Legal Forms of Implementation of Foreign Tax Policy in the Context of European Integration of Ukraine - CHAIKA, Viktoriia V.; KASIANENKO, Liubov M.; LATKOVSKA, Tamara A.; PRYSHVA, Nadiia Yu.; TOPCHII, Vasyl V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).10, 2019)
The article defines the basic legal forms of implementation of the foreign tax policy of Ukraine. Particular attention is paid to characterizing the features of the EU tax policy. The assessment of the current state of approximation of the Ukrainian tax legislation to the EU standards is based on the legal analysis of the provisions of the Association Agreement between Ukraine and the EU and other regulations. The issue of approximation of the Ukrainian tax legislation to the acquis communitaire in the field of energy taxation has been updated. The legal forms of tax cooperation between Ukraine and the OECD are analyzed. The following areas of Ukraine's foreign tax policy are emphasized: joining the BEPS Action Plan and the Multilateral Convention to Implement Tax Treaty Related Measures to Prevent Base Erosion and Profit Shifting. The legal description of certain provisions of bilateral agreements of Ukraine with the EU Member States and OECD in the area of avoiding double taxation of income and property is provided. On this basis, the conclusion is made about the decisive role of the contractual legal form in the process of implementing the foreign tax policy of Ukraine.